Music: an alternative for improving the adult woman's quality of life - Freddy Durán-Montero; Ana Vilma Colas-Pavón (Universidad de Guantánamo, 2015)
In this paper a set of activities combined with music are proposed for improving the quality of life of elder women in homes in "La Asunción" of the Baracoa municipality, it allows teachers to teach with better quality. Varied exercises and greater motivation were granted with the activities developed as part of the physical and recreational activities that have been created considering needs, limitations and possibilities; they go from dancing and physical activities to outdoor activities in close relationship with nature. Different methods were used to collect information from the professors in contact with the groups of elder people and observation to diagnose the present-day situation and problems. These activities with music aim at achieving the grandmothers' incorporation to the physical recreational activities as a way to improve health and achieve better quality of life.